IMPROVING FIXED ASSETS ACCOUNTING IN ENTERPRISES - Misirov Asliddin Mamasobirovich (Ecominds Press, 2026)
In today's competitive environment, especially in construction companies, the condition and utilization of fixed assets play a crucial role. This article explores the system of accounting for fixed assets in companies, its current state, and ways to improve it. Proper accounting, valuation, and depreciation processes of these assets are of great importance for many companies. The article analyzes traditional methods of accounting for fixed assets, existing problems, and modern approaches in the field of accounting. Additionally, the article provides suggestions regarding the reflection of fixed assets in accounting, their inventory management, and depreciation calculations. The study also offers recommendations for improving the accounting of fixed assets by introducing digital technologies, automating processes, and adhering to international accounting standards. This article provides practical recommendations for making fixed asset accounting more effective and accurate.
Keywords: Fixed assets, accounting, depreciation, inventory, calculations, automation, digital technologies, international accounting standards, company, fixed asset analysis, accounting system.